Characterization of thin copper films on Ni(111) by CO titration - Held, Georg; Sklarek, Werner; Mayan, M.; Steinrück, Hans-Peter (Surface Science, 1998)
Ultra-thin copper films on Ni(111) (Θ ≤ 1 ML) were studied by the adsorption of CO followed by high resolution X-ray photoelectron spectroscopy. Saturating the surface at 100 K with CO leads to adsorption on the entire surface, i.e. Cu-covered as well as bare Ni(111) areas. Upon annealing to 220 K the Cu-bonded CO molecules desorb leaving only the Ni-areas covered with CO. High resolution XPS spectra in the O 1s and Cu 2p regime have been recorded after adsorption at 100 K and after annealing to 220 K. The total area of Ni-terminated surface regions can be determined from the integrated O 1s XPS intensities after annealing; from the linear decrease of this area versus the amount of adsorbed copper a two-dimensional growth mode can be identified for layers which are annealed to 800 K. In addition, the CO adsorption sites on the Cu-terminated as well as on the Ni-terminated parts of the surface can be determined from the corresponding O Is binding energies. The changes in the O 1s peak shapes with increasing Cu coverage lead to the conclusion that the adlayers have a very high island density. © 1998 Elsevier Science B.V. All rights reserved.